Persistence of skin-deep resilience in African American adults. - Gene H. Brody; Tianyi Yu; Edith Chen; Gregory E. Miller (2020)
Objective: The skin-deep resilience pattern suggests that, for low-socioeconomic-status African American youths, the ability to maintain high self-control and to persist with efforts to succeed may act as a double-edged sword, facilitating academic success and adjustment while undermining physical health. We extend research by following a sample of rural African Americans, asking whether the skin-deep resilience pattern, evident during adolescence, persists into adulthood by increasing susceptibility to metabolic syndrome (MetS) and insulin resistance (IR). Methods: The sample included 368 11-year-old African Americans, their parents, and their teachers. Parents provided data on family poverty across ages 11–18 years. Teachers provided data on youths’ planful self-control across ages 11–13 years. At age 27 years, participants completed questionnaires about educational attainment and psychological adjustment and provided a fasting blood sample from which MetS and IR were assessed. Results: Regardless of years spent living in poverty, planful self-control during childhood was associated with college graduation (p < .001) and with low levels of depressive symptoms (p = .016) and antisocial behavior (p = .028). For participants exhibiting high levels of self-control, however, living more years in poverty across adolescence was associated with a greater number of MetS components that met clinical cutoff criteria (p = .018) and greater IR (p = .016) during adulthood. Conclusions: The skin-deep resilience pattern persists into adulthood, particularly among those who spent more of their adolescence living in poverty, and increases vulnerability to MetS and IR while it also promotes college graduation and positive psychological adjustment. (PsycInfo Database Record (c) 2020 APA, all rights reserved)